Trajetória do estudante de escola pública nas faculdades de Letras do Grande ABC - Ferreira, Jean de Oliveira (2010)
This study investigated the trajectory of graduate students in public schools high school who enrolled in a Faculty of Arts at a private university in the region and the ABC were formed between the years 2009 and 2010. These students surveyed are not benefiting from the social inclusion program created by the federal government called the "University for All - PROUNI. We tried to understand the gains and difficulties in the path of those coming from public school students in college. We could understand the relationship between knowledge and experienced in the Region choice by way of letters, to know the profile of the students and their professional perspectives that existed before joining the course and which came into existence after college. To analyze the trajectory of these subjects, we collected data using the instrument as a questionnaire with open and closed, applied to 28 students. We did a quantitative analysis, in order to characterize the subjects, and qualitative, in order to reap these subjects views on the topic in question. The authors use that are tied to the issues addressed in the work content. They are APPLE (2006), Lahiri (1997), Bourdieu (2007), Masetto (2003), Freire (2003), Rodrigues (2007), among others